Effectiveness Analysis Of The Corporate Social Responsibility (CSR) Program Of Pt. Toba Pulp Lestari Tbk For Improving The Welfare And Quality Of Human Resources At Parmaksian District Society - Butar-Butar, Josua; Siregar, Onan Marakali (SEAN Institute, 2023)
Corporate Social Responsibility is a form of responsibility from the company for social life and the environment both within the company and around the company. PT. Toba Pulp Lestari Tbk is here to provide Corporate Social Responsibility programs, especially in Parmaksian District where the company was founded. However, there is still news that PT. Toba Pulp Lestari Tbk does not give enough care to the community and operational activities that have a negative impact on the community, causing protests for the company. This study aims to analyze how that is conducted by PT. Toba Pulp Lestari Tbk and analyze how the effectiveness of the implemented programs for improving the welfare and quality of human resources in the Parmaksian District society during 2020-2021. So that it can be known whether the implemented programs by PT. Toba Pulp Lestari Tbk company are running effectively. This study uses a qualitative method which aims to describe the phenomena that is occured. Data collection techniques that are used in this study are interviews, observation and documentation. This study collects information from interviewing informants consisting of key informants, main informants and additional informants. The data analysis technique uses the data reduction process, data presentation and discussion. The results of this study indictaes that the Corporate Social Responsibility programs of PT. Toba Pulp Lestari is running well and effectively in improving the welfare and quality of human resources of the Parmaksian District society during 2020-2021. However, there are still many Corporate Social Responsibility programs that need to be improved and added by PT. Toba Pulp Lestari so that the public welfare and the quality of human resources in the Parmaksian District community will be more advanced and better.